2013
DOI: 10.1108/jmp-12-2012-0399
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing workplace bullying: the buffering effects of contextual factors

Abstract: Purpose. This paper examines the direct and buffering effects of three workplace contextual factorsconstructive leadership, perceived organizational support, and organizational antibullying initiativeson bullying and its relationships with relevant criteria. Further, the paper investigates the effectiveness of organizational initiatives against bullying as perceived by targets and non-targets. Method. Data were collected from 727 employees in nine New Zealand healthcare organizations. Of these, 133 employees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 97 publications
2
87
0
Order By: Relevance
“…With respect to organisational leadership, our findings indicate that production and achievement‐oriented leadership style is a protective factor for workplace bullying among junior doctors. In relation to the findings of previous studies, many have focused on the relationship between autocratic leadership, laissez‐faire leadership, transformational leadership, authentic leadership, ethical leadership, constructive leadership, and workplace bullying. None have examined the relationship of production and achievement‐oriented leadership style with workplace bullying specifically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to organisational leadership, our findings indicate that production and achievement‐oriented leadership style is a protective factor for workplace bullying among junior doctors. In relation to the findings of previous studies, many have focused on the relationship between autocratic leadership, laissez‐faire leadership, transformational leadership, authentic leadership, ethical leadership, constructive leadership, and workplace bullying. None have examined the relationship of production and achievement‐oriented leadership style with workplace bullying specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Organisational support has been defined as “employees' global beliefs concerning the extent to which the organisation values their contributions and care about their well‐being.” Its specific antecedents include support from agents of organisations such as superiors and human resource management systems that recognises the importance of human capital . The findings of previous studies indicate that organisational support is significantly related to workplace bullying . In the context of junior doctors' work environments, it is assumed that low organisational support may perpetuate bullying at work.…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, we respond to Nielsen and Einarsen’s () call for empirical assessments of moderating variables that can attenuate the effects of bullying. In line with the job demands–resources theory, and following previous research (e.g., Cooper‐Thomas et al, ), we refer to workplace bullying as a job demand, while job autonomy and occupational self‐efficacy are considered as resources. Our proposed model is presented in Figure .…”
Section: Introductionmentioning
confidence: 89%
“…For example, Djurkovic et al ( 2008 ), in a sample of 335 schoolteachers, found that workplace bullying was more strongly related to employees' intention to leave the organization among participants who perceived low organizational support than among participants who perceived high organizational support (in this condition the effects of bullying on intention to leave were non-significant indeed). In a similar vein, Cooper- Thomas et al ( 2013 ) indicated that perceived organizational support buffered the relationship of bullying with self-rated job performance in a sample of 727 New Zealand employees from nine healthcare organizations.…”
Section: Introductionmentioning
confidence: 90%